Analysis Of Maxim On Danseigo Joseigo Form In Anime Kimi No Nawa (Architecture Image Studies, 2025)
This study analyzes the application of Grice's maxims in the use of danseigo (male language) and jo-seigo (female language) in the anime Kimi no Na Wa. It focuses on how conversational maxims are fol-lowed or violated and how gendered language influences character interactions. Using a descriptive quali-tative method, 56 dialogues were examined through non-participant observation and recording. Results show that 49 dialogues adhered to the maxims, while 7 violated them, particularly the maxims of quality and relevance. The use of danseigo and joseigo highlights gender traits and interpersonal dynamics among the characters.